2014
DOI: 10.1159/000361055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fetal Growth by Customized Growth Charts

Abstract: Customized fetal growth charts take account of the individual variation in the fetal growth potential based on non-pathological maternal and fetal characteristics. Application of these customized weight charts might improve the distinction between pathological growth-restricted fetuses and fetuses that are small but have reached their growth potential. Current models for customized growth standards have been based on birth weight and fetal growth data. Variables used for customization are gestational age, mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…These ultrasound examinations were used to establish gestational age and to assess fetal growth patterns [35, 36]. These methods have previously been described in detail [3739].…”
Section: Measurementsmentioning
confidence: 99%
“…These ultrasound examinations were used to establish gestational age and to assess fetal growth patterns [35, 36]. These methods have previously been described in detail [3739].…”
Section: Measurementsmentioning
confidence: 99%
“…It is well-established that newborns born SGA or LGA may be both constitutionally or pathologically small or large for their gestational age [39]. It has been suggested that newborns who are pathologically small or large for their gestational age due to abnormal fetal growth have increased risks of morbidity and mortality, as compared to those newborns who are constitutionally small or large for their gestational age [39].…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…As appropriate as it may appear, this particular definition is impractical due to the challenge of assessing the genetic potential of a certain individual. Newer diagnostic tools allowing the longitudinal evaluation of fetal growth in a noninvasive fashion and the current development of fetal growth trajectories have been proposed as an alternative to assess growth potential and IUGR (127,403). In this regard, premature infants represent an interesting group since they are usually born small but may be appropriate for their gestational age.…”
Section: B Defining Birth Weightmentioning
confidence: 99%